Demographic risk factors for COVID-19 infection, severity, ICU admission and death: a meta-analysis of 59 studies - Pijls, Bart G; Jolani, Shahab; Atherley, Anique; Derckx, Raissa T; Dijkstra, Janna I R; Franssen, Gregor H L; Hendriks, Stevie; Richters, Anke; Venemans-Jellema, Annemarie; Zalpuri, Saurabh; Zeegers, Maurice P (BMJ open, 2021)
ObjectiveWe aimed to describe the associations of age and sex with the risk of COVID-19 in different severity stages ranging from infection to death.DesignSystematic review and meta-analysis.Data sourcesPubMed and Embase through 4 May 2020.Study selectionWe considered cohort and case–control studies that evaluated differences in age and sex on the risk of COVID-19 infection, disease severity, intensive care unit (ICU) admission and death.Data extraction and synthesisWe screened and included studies using standardised electronic data extraction forms and we pooled data from published studies and data acquired by contacting authors using random effects meta-analysis. We assessed the risk of bias using the Newcastle-Ottawa Scale.ResultsWe screened 11.550 titles and included 59 studies comprising 36.470 patients in the analyses. The methodological quality of the included papers was high (8.2 out of 9). Men had a higher risk for infection with COVID-19 than women (relative risk (RR) 1.08, 95% CI 1.03 to 1.12). When infected, they also had a higher risk for severe COVID-19 disease (RR 1.18, 95% CI 1.10 to 1.27), a higher need for intensive care (RR 1.38, 95% CI 1.09 to 1.74) and a higher risk of death (RR 1.50, 95% CI 1.18 to 1.91). The analyses also showed that patients aged 70 years and above have a higher infection risk (RR 1.65, 95% CI 1.50 to 1.81), a higher risk for severe COVID-19 disease (RR 2.05, 95% CI 1.27 to 3.32), a higher need for intensive care (RR 2.70, 95% CI 1.59 to 4.60) and a higher risk of death once infected (RR 3.61, 95% CI 2.70 to 4.84) compared with patients younger than 70 years.ConclusionsMeta-analyses on 59 studies comprising 36.470 patients showed that men and patients aged 70 and above have a higher risk for COVID-19 infection, severe disease, ICU admission and death.PROSPERO registration numberCRD42020180085.